ПРОЕКТУВАННЯ ТА РЕАЛІЗАЦІЯ ІНФОРМАЦІЙНОГО ВЕБ-САЙТУ КАФЕДРИ ЗАКЛАДУ ВИЩОЇ ОСВІТИ - KHOVAYBA , Daryna; DIDKOWSKY, Ruslan (Cherkasy University Bulletin: Applied Mathematics. Informatics, 2023)
Introduction. In today’s digital world, information technology plays a crucial role in every field, including education. Websites have become essential tools for higher education institutions as they provide an effective means of communication with students, faculty, and other stakeholders. The primary goal of this work is to design and implement a website for a department, which will enhance communication, ensure access to necessary information, and improve interaction with students, faculty, and other interested parties. The purpose of this article is to design and implement an informational website for a department of a higher education institution. Results. The article examines the process of developing an informational website for the Department of Applied Mathematics and Informatics at a higher education institution. It describes the stages involved, including requirement analysis for the site, designing the structure and layout, creating an interactive prototype in Figma, and setting up the CMS platform. The website aims to ensure effective communication between students, faculty, and administration, as well as enhance the institution’s image. Key sections of the site include information about the department, resources for students, news, and contact details. The use of modern graphic elements, fonts, and color schemes contributes to the site’s attractiveness and functionality. Special attention is given to the choice of CMS for content management, with WordPress selected for its simplicity, functionality, and extensive community support. The final stages include the installation and configuration of WordPress on a web hosting server, completing the development process. The article highlights key aspects of creating an effective web resource for an educational institution. Conclusion. The article presents a study on the design and implementation of an informational website for a department of a higher education institution. Designing and implementing such a website is an important and relevant task that contributes to the improvement of the educational process, communication, and the prestige of the institution. The results of the study can be applied in practical activities for the development and deployment of a department’s website using tools such as Figma and WordPress. The main outcomes of the work include:  a review of existing work and approaches to designing websites for higher education departments, along with an analysis of the subject area;  an analysis of the requirements for the department’s website, including the selection of colors and fonts for the site;  the development of the website structure and the design of page layouts, with the website design created in Figma;  proficiency in the CMS WordPress was developed and applied;  the implementation of the website design on CMS WordPress and the deployment of the website on a web hosting server.